TEKNIK BELAJAR UNTUK MENINGKATKAN KEMAMPUAN BERKOMUNIKASI DALAM BAHASA INGGRIS BAGI MAHASISWA NON-JURUSAN BAHASA INGGRIS - Nashruddin Nashruddin (Scolae: Journal of Pedagogy, 2019)
For students of English department, it is obviously the main part to direct them to be proficient in communicating using English, but for non-English department, this is something unusual, even it tends to be heavy for them. The problems that then arise are what learning techniques are appropriate and interesting for them to apply to be proficient, and how they apply those learning techniques. Therefore, research question of this study are: (i) what learning techniques are applied students of STIKES RSU Daya Makassar? (ii) How are those learning techniques applied by students of STIKES RSU Daya Makassar? This research aims to: (i) study learning techniques for students of STIKES RSU Daya Makassar to apply (ii) Explore how those learning techniques applied in communicating in English by students of STIKES RSU Daya Makassar. This study is a qualitative research in the form of case study. The results of this research indicate: (i) students of STIKES RSU Makassar apply three learning techniques, namely effective production technic, comprehension reaction technic, and reinforcing comprehension technic. (ii) Each technique used by students, is applied by switching, getting help, using gesture, taking notes, translating, and using resources.